Inovasi Supervisi Berbasis Web: Mitigasi Hambatan Sosiologis dan Senioritas Melalui Digital Leadership - M. Aditya Prayoga; Muhammad Anggung Manumanoso Prasetyo (JoIEM (Journal of Islamic Education Management), 2026)
Conventional academic supervision in Madrasah environments often faces sociological barriers such as subjectivity bias and a rigid culture of seniority. This study aims to analyze the role of digital leadership through the implementation of a web-based supervision system in mitigating these barriers and enhancing teacher professionalism. Employing a qualitative case study approach at MAS Ulumuddin, the research explores how the digitalization of instruments transforms leadership oversight dynamics. Findings indicate that the web-based system effectively differentiates between managerial and academic domains, shifting leadership focus from physical bureaucracy to substantive professional dialogue. Score automation proved effective in reducing the psychological barriers of leaders toward senior teachers, transforming hierarchical-personal relationships into data-driven partnerships and reflections. The integration of the Glickman Model into the digital system enables precise teacher typology mapping to determine adaptive coaching styles whether directive, collaborative, or non-directive. The research novelty lies in the repositioning of technology as a sociological mediator that neutralizes interpersonal friction within the organization. The model's success relies heavily on three pillars of digital leadership: technical proficiency, database management, and a humanistic approach. The study offers a prototype for modern, accountable Madrasah governance through the synergy of infrastructure and human resource change management.